ANALISIS PERBANDINGAN KEKUATAN TARIK HASIL PENGELASAN SMAW DAN MIG PADA PELAT ASTM A 36 - Dedy Irawan; Rachmasari Pramita Wardhani (MECHA JURNAL TEKNIK MESIN, 2020)
This Research aims to analys the result of the tensile strength of workpieces and learn the different of tensile strength to both the welding methods commonly used in the mining industry, SMAW (Shield MetalArc Welding) and MIG (Metal Inert Gas) welding methods. The result of analysis work piece strength testis the value of tensile strength obtained by conducting tensile strength testing. In the process of weldingworkpiece used materials ASTM A 36. Key words : SMAW, MIG, Tensile Strength and ASTM A 36.